Emotional Intelligence and Learning Interest in Improving Civics Learning Outcomes for Fifth Grade of Elementary Schools - Kusumawardani, Andina Widya; Widodo, Susilo Tri (Jurnal Pedagogi dan Pembelajaran, 2024)
The current fact is that students' Civics learning outcomes are still in the low category. There are various factors that cause low student learning outcomes. This research aims to examine the significant relationship between emotional intelligence and students' interest in learning on students' Civics learning outcomes. This research is included in a quantitative approach with a correlational research type. The population in this study was 179 fifth grade elementary school students. Sample determination was carried out using probability sampling techniques. The number of samples in this study was rounded up to 124 students. The data collection methods used questionnaires and documentation studies. The data was analyzed using inferential statistics. The results of data analysis using Pearson Product Moment show that there is a significant relationship between emotional intelligence and student Civics learning outcomes. Apart from that, there is also a significant relationship between interest in learning and students' Civics learning outcomes. Based on the results of the multiple correlation test, it is known that there is a significant relationship between emotional intelligence and interest in learning and student Civics learning outcomes. It was concluded emotional intelligence and high interest can improve student learning outcomes. The implication of this research is emotional intelligence and interests must be considered by every teacher, so that students have a high enthusiasm for learning so they can improve Civics learning outcomes.. The latest information on the results of this research can be used as a parameter for developing students' emotional intelligence and interest in learning.